The Polyptych of Saint Germain-des-Pres: peasant agriculture and commerce in the ninth century Paris Basin - Buck, Effie (My University, 1985)
Using the Polyptych of Saint Germain-des-Prés as a source, this study examines the nature and extent of peasant involvement in the marketplace in the ninth century Paris basin. A minority of the 1556 manses in the sample were found to be involved in commercial agriculture, paying cash rents which seem to have been raised mainly by the sale of wine. Some manses were found to have vineyards with productive capacities well in excess of reasonable domestic need, suggesting a regular and planned surplus. Involvement in the marketplace was found to exacerbate economic inequalities within the ranks of the dependent peasantry.
Keywords: History; History